Endoscopic mucosal resection is effective for laterally spreading lesions at the anorectal junction. Issue 4 (12th November 2019) - Shahidi, Neal; Sidhu, Mayenaaz; Vosko, Sergei; van Hattem, W Arnout; Bar-Yishay, Iddo; Schoeman, Scott; Tate, David J; Holt, Bronte; Hourigan, Luke F; Lee, Eric YT; Burgess, Nicholas G; Bourke, Michael J
Abstract : Objective: The optimal approach for removing large laterally spreading lesions at the anorectal junction (ARJ-LSLs) is unknown. Endoscopic mucosal resection (EMR) is a definitive therapy for colorectal LSLs. It is unclear whether it is an effective modality for ARJ-LSLs. Design: EMR outcomes for ARJ-LSLs (distal margin of ≤20 mm from the dentate line) in comparison with rectal LSLs (distal margin of >20 mm from the dentate line) were evaluated within a multicentre observational cohort of LSLs of ≥20 mm. Technical success was defined as the removal of all polypoid tissue during index EMR. Safety was evaluated by the frequencies of intraprocedural bleeding, delayed bleeding, deep mural injury (DMI) and delayed perforation. Long-term efficacy was evaluated by the absence of recurrence (either endoscopic or histologic) at surveillance colonoscopy (SC). Results: Between July 2008 and August 2019, 100 ARJ-LSLs and 313 rectal LSLs underwent EMR. ARJ-LSL median size was 40 mm (IQR 35–60 mm). Median follow-up at SC4 was 54 months (IQR 33–83 months). Technical success was 98%. Cancer was present in three (3%). Recurrence occurred in 15.4%, 6.8%, 3.7% and 0% at SC1–SC4, respectively. Among 30 ARJ-LSLs that received margin thermal ablation, no recurrence was identified at SC1 (0.0% vs 25.0%, p=0.002). Technical success, recurrence and adverse events were not different between groups, except for DMI (ARJ-LSLs 0% vs rectal LSLs 4.5%, p=0.027). Conclusion: EMR is an effective technique for ARJ-LSLs and should be considered a first-line resection modality for the majority of these lesions.